MOLECULAR GENETIC ANALYSIS OF MICRODELETIONS OF Y-CHROMOSOME AZF LOCUS - Kairzhanova , A.D.; Kamalova , D.K.; Abisheva , G.D.; Amirgazin , A.O.; Shvedyuk , V.B.; Popova , O.A.; Kim , G.M.; Shevtsov , A.B. (Eurasian Journal of Applied Biotechnology, 2016)
Male infertility plays a significant role in reproduction. Although medical therapy can successfully treat ejaculation disorder and impotence,a majority of genetic disorders remain therapeutically intractable. Y-chromosome deletions are the most common causes of male infertility. The distal end of the Y-chromosome long arm bears the locus of azoospermia factor (AZF), which carriesgenes essential for spermatogenesis. Microdeletions inthe Y-chromosome long arm are associated with spermatogenesis disorder and are the most common genetic cause of oligospermia(5-10%) and azoospermia(10-15%). In our study, we analysed microdeletions of the AZF locus, using sixSTS markers (recommended by the European Association of Andrology),two gene controls for reaction inhibition, and a Y-chromosome control. We tested DNA samples of 138 male subjects with the developed testsystem. The distribution results of microdeletions of the Y-chromosome AZF locus were obtained for samples from the Kazakh population. Deletion of the AZF locus was reported in11% of males with oligospermia and 16% males (7 of 45 subjects)with azoospermia.